Perception of the educational environment by foreign students of medical and dental faculties of the Dnepropetrovsk Medical Academy. - N. V. Stanishevska; D. G. Marchenko (Морфологія, 2019)
Background. Favorable educational environment is the key to successful adaptation of both domestic and foreign students to the requirements of modern training programs. The perception by students of the educational environment requires constant study, since it reflects the internal processes taking place in the student's environment, which characterizes the learning process as a whole. Objective. This investigation was aimed at studying the perception by foreign students of medical and dental faculties of 1st and 2d courses of the Dnipropetrovsk Medical Academy educational environment. Methods. As a method was used Dundee Ready Education Environment Measure (DREEM). DREEM is a questionnaire consisting of 50 statements. All questions are subdivided into five categories: students' perception of learning or learning; teacher perception of pupils or teaching; academic self-perception; educational atmosphere and social self-perception of students. Results. The study involved 200 foreign students. The mean total DREEM score of the educational environment was 139/200 (70%) and the majority of students had positive rather than negative perceptions, which can be regarded as quite good conditions of the educational process. Students rated academic self-perception as high –23.8 / 32 (74%). No less appreciated was the perception of learning –34.7 / 48 (72%). The perception of the educational atmosphere –32.6 / 48 (68%) and the perception of teaching –29.9 / 44 (68%) students rated equally and well above average, but social self-perception was reduced –18.5 / 28 (66% ). Conclusion. The survey made it possible to assess the perception of the educational environment by foreign medical students of 1 and 2 courses of the Dnipropetrovsk Medical Academy. The educational environment was characterized by the students as positive in general, but with certain disadvantages. Analysis of scores according to all criteria can serve as a basis for the correction of teaching methods, relations between teachers and students, which will contribute to the improvement of the educational process.